Ocular Toxoplasmosis: an Update - Garweg, J. G. (Klinische Monatsblätter für Augenheilkunde, 2016)
Introduction: Although the seroprevalence of toxoplasmosis has undergone a progressive 50 % decline during the past 20 years, the disease remains an economically important health hazard in many countries. Ocular toxoplasmosis (OT) is the most frequent cause of infectious posterior uveitis, and new insights into its pathophysiology have paved the way for new therapeutic strategies. Methods: This review summarises recent insights into the disease, its clinical manifestations and therapeutic options. The data have been gleaned from a PubMed search, which was conducted in August 2015 using the key term “ocular toxoplasmosis”. Results: A laboratory confirmation of the diagnosis serves as the basis for estimating the clinical burden of OT. This is more severe in South America than in Europe, due to the higher incidence of the more virulent New World parasitic strains. It is not yet possible to differentiate between acquired and congenital cases in most patients. However, in elderly individuals, clinical manifestations of acquired OT are more frequently encountered and in atypical forms. Although inflammation may initially be more pronounced in acquired than in congenital cases of OT, the final visual acuity is usually better and the risk of recurrence lower. Amongst the numerous therapeutic options, none is clearly superior. In immunocompromised individuals and in those with frequent recurrences, prophylactic measures should be considered. Conclusion: OT is still a potentially vision-threatening affection, namely in elderly individuals with acquired disease and in those patients harbouring the more aggressive New World strains of the parasite. Owing to the limitations in diagnostic sensitivity and therapeutic efficacy, treatment strategies have to be tailored to the individual needs.
Keywords: ocular toxoplasmosis; pathophysiology; burden of disease; diagnostics; therapy; prophylaxis; review